LEARNENGLISH TEENS: AN AI-MEDIATED TEACHING SPEAKING SKILL IN THE EFL CLASSROOM - Ida Royani (Universitas PGRI Palembang, 2025)
Technological advances in teaching English have been established to support interesting media and authentic learning materials in language classes. This study investigates the implementation of internet-based media in the intermediate-speaking class provided by LearnEnglish Teens on the British Council Online Course. Using a qualitative descriptive research design, an exploration of the integrated activities in the classroom was observed using field notes. The results reveal that LearnEnglish Teens has a dynamic class atmosphere where students and lecturers can integrate fragment language skills into an integrative proficiency of language use by providing class stages to practice. Meanwhile, the negotiated activities in the class driven by the lecturer had also been described in detail in each stage such as regulating turn-taking, repetition, impulsive correction, assertive treatment, unlocking creativeness, equipping speaking organization, and generating useful expressions in specific- individualized practices.